Algae of Betana pond and its relationship with water paramers - Rai, Shiva Kumar; Adhikari, Taranidhi (Nepalese Journal of Biosciences, 2018)
Algal flora of Betana wetland, their monthly variation, and their relationship with water parameters have been studied. Floating, epiphytic and benthic algae were collected monthly for up to seven months. Out of the total genera (61) observed, only 32 algae were identified up to the species level. The largest class was Bacillariophyceae with 32% algal genera. Similarly, maximum number of genera (93.44%) were found as epiphytic form. Cymbella was the dominant genus whereas Synedra, Cocconeis, Gomphonema, Pinnularia, Spirogyra, Oscillatoria, Cosmarium and Navicula were common genera in the pond. The largest number of genera (68.85%) were found in June and July. The average water temperature of the pond was maximum (32.66°C) in July and minimum (24.25°C) in December and average DO was maximum (8.52 mg/l) in August and minimum (7.2 mg/l) in June. The average pH of water ranges from 7.29 to 7.74. DO and the total number of genera were found to be significantly correlated and the value of correlation coefficient (r) was negative. Water temperature and total number of genera were found to be correlated. Similarly, the pH of watter and number of epiphytic genera were also found to be significantly correlated.